2015
DOI: 10.1111/evj.12384
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of seven methods for continuous therapeutic cooling of the equine digit

Abstract: Immersion of the foot and at least the pastern region in ice and water achieved sustained HWST <10°C as did a prototype perfused cuff device with a dry interface. Variation between cooling methods may have a profound effect on HWST and therefore efficacy in clinical cases where laminitis prophylaxis or therapy is the goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…We can then speculate that due to the reduction of the surface temperature of the limb post-ice boot, there is also a reduction of the temperature of the soft tissue beneath the skin in that area. To investigate further, studies have shown that the application of the standard melting ice cools better than gel wraps and chemical ice envelopes (Van Eps and Orsini, 2016), so a study could be done evaluating the difference between commercially available ice boots and standard melting ice. Results of this study indicate the usefulness of these ice boots on horses to reduce the surface temperature of the horse's legs and furthermore the temperature of the soft tissue beneath the skin.…”
Section: Resultsmentioning
confidence: 99%
“…We can then speculate that due to the reduction of the surface temperature of the limb post-ice boot, there is also a reduction of the temperature of the soft tissue beneath the skin in that area. To investigate further, studies have shown that the application of the standard melting ice cools better than gel wraps and chemical ice envelopes (Van Eps and Orsini, 2016), so a study could be done evaluating the difference between commercially available ice boots and standard melting ice. Results of this study indicate the usefulness of these ice boots on horses to reduce the surface temperature of the horse's legs and furthermore the temperature of the soft tissue beneath the skin.…”
Section: Resultsmentioning
confidence: 99%
“…fluids, and less commonly used agents include polymixin B, enteral adsorbents, and plasma . Cryotherapy of the distal limbs can attenuate lamellar damage and should improve management of horses at risk or that develop laminitis from perioperative sepsis .…”
Section: Role Of Post‐operative Pharmacological Managementmentioning
confidence: 99%
“…pro-inflammatory cytokine expression in multiple disease processes, targeted therapy through hypothermia for these individual processes has been the focus in both human (Crouser 8 2012, Coyan et al 2014, Yuan et al 2014) and now veterinary medicine (van Eps and Pollitt 2004, van Eps 2010, Kullmann et al 2014, van Eps et al 2014, van Eps and Orsini 2016. Hypothermia has been documented to decrease leukocyte infiltration and cytokine expression, leading to decreased end organ inflammation and injury in multiple disease states in humans and animal models of human disease (Crouser 2012, Rim et al 2012, Yenari and Han 2012, Coyan et al 2014, Yuan et al 2014.…”
Section: Introductionmentioning
confidence: 99%